The Activity of Combination of Ethanol Extract of Artocarpus lacucha Buch.-Ham and Anredera cordifolia Steenis Leaves to Increase Wound Healing Process on NIH-3T3 Cell Line - Nazliniwaty, Nazliniwaty; Hanafiah, Olivia Avriyanti; Pertiwi, Dewi; Muhammad, Mahatir; Satria, Denny (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aims to determine the effect of the combination of ethanol extract of Artocarpus lacucha Buch.-Ham and Anredera cordifolia Steenis leaves to increase cell proliferation and increase VEGFR-2 expression of NIH-3T3. METHODS: The samples used were Artocarpus lacucha Buch.-Ham and Anredera cordifilia Steenis leaves. The powder of simples was extracted using ethanol 80% with maceration method. The effect of extract combination on proliferation was evaluated using the MTT method. Wound healing assay was established by a cell migration method, and VEGFR-2 expression was determined using RT-PCR. RESULTS: The effect of combination of ethanol extract of Artocarpus lacucha leaves (EEALL) and ethanol extract of Anredera cordifolia leaves (EEACL) on cell proliferation after 24h, 48h and 72h incubation found as viable cells were showed (124.33 ± 0.32%; 128.52 ± 0.41%; 118.35 ± 0.22%). Percent of wound closed after 24 h and 48 h incubation are 64.88 ± 0.90% and 100.00 ± 0.00%, and expression of VEGFR-2 increased from 1 (control) to 1.58 ± 0.02. CONCLUSION: The results suggest that a combination of EEALL and EEACL (37.5 μg/mL−37.5 μg/mL) is effective in increasing cells proliferation and hence wound healing process.